Sensitivity Characterization of an Impedance-Based Platform for Viability Analysis of 3D Spheroids - Claudia Sampaio da Silva; Christian Beyer; Julia Boos; Sreedhar Kumar; Mario Modena; Thomas Valentin; Andreas Hierlemann; Vincent Revol (Proceedings)
Electrical impedance spectroscopy (EIS) is a promising label-free tool for high-throughput analysis of 3D cellular constructs, also called spheroids. Here, we used an EIS platform featuring facing electrodes to characterize the viability of hepatic spheroids, which are used for bioprinting applications. By using principal component analysis (PCA), we show that this simple impedance sensor enables us to successfully distinguish healthy spheroids from spheroids exposed to toxic conditions. The sensitivity of the impedance sensor will be further characterized by using spheroids exposed to varying stress conditions like different drug concentrations and temperatures.